THE ROLE OF TRANSFORMATIVE LEADERSHIP IN PROMOTING JOB SATISFACTION IN BASRA OIL ENTERPRISES - Alsadoon, Abdulrazak Amer Adnan (PT. Antis International Publisher, 2024)
Objective: This study examines the impact of transformative leadership on job satisfaction among employees in Basra's oil industry, focusing on the Rumaila and Zubair oil fields.To explore how leadership dimensions—Inspirational Motivation, Individualized Consideration, Intellectual Stimulation, and Idealized Influence—individually and collectively influence employee job satisfaction. Method: A descriptive correlational design was employed, with data collected via a structured questionnaire from 250 respondents (91% response rate) selected through random sampling. The 25-item questionnaire used a 5-point Likert scale to measure leadership practices and job satisfaction. Data were analyzed using SPSS, including descriptive statistics, Pearson correlation, and multiple regression analysis. Results: Significant positive correlations were identified between all leadership dimensions and job satisfaction, with Idealized Influence showing the strongest impact (r = 0.67, β = 0.32, p < 0.01). The model explained 55% of the variance in job satisfaction, highlighting the substantial role of transformative leadership. Novelty: This study fills a gap in understanding the relationship between transformative leadership and job satisfaction within the oil sector in Iraq, emphasizing the need for leadership development programs to foster employee well-being in challenging industrial environments. These findings offer valuable insights for policymakers and managers aiming to enhance organizational outcomes through effective leadership.